Pengaruh Leverage Pada Perataan Laba dengan Good Corporate Governance Sebagai Variabel Pemoderasi - Pande, I Made Andika Pramana; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2017)
ABSTRACT The purpose of this study is to determine the ability of good corporate governance as moderating the influence of leverage on income smoothing. Income smoothing is a reduction in fluctuations in earnings from year to year by moving income from high years of income to less favorable periods. One factor that allegedly influences the actions of managers in making income smoothing is leverage. This study was conducted on all companies listed in Indonesia Stock Exchange (BEI) and included in the ranking of corporate governance perception index (CGPI) period 2011-2015. The number of samples taken as many as 18 companies, with non-probability sampling method with purposive sampling technique. Data collection methods used were non participant observation and data analysis techniques used were descriptive analysis test, logistic regression analysis and Moderating Regression Analysis (MRA). The results of the study found that leverage has a significant positive effect on income smoothing. Good corporate governance as moderator weakens the influence of leverage positive relationships on income smoothing.   Keywords: :       good corporate governance , leverage , income smoothing